Transaksi Bisnis Online dalam Perspektif Islam - Pujiyanti, Siti Dwi; Wahdi, Anis (LPMP Imperium, 2020)
Purpose-The purpose of this research is to find out and explore the online business transactions implemented by the Tokopedia application and online business transactions in the Islamic perspective on the Tokopedia application case study. Methods- This study is a qualitative research method, namely by using the Library Search (Literature Review) field by taking references from several books and sources from websites or the internet. Findings- From the results of this study, it can be concluded that the transaction of buying and selling online on the Tokopedia application is perfectly legal in Islamic law. As long as there is no element of deception or fraud or the desired item is incomplete or defective (not as expected) that occurs during the transaction process. Even if this happens, the responsible party is obliged to return all buyer's money and the sale and purchase is considered invalid because it does not meet the trading agreement.